Production of Nanocrystalline Cellulose from Cassava Stems Using Hydrochloric Acid Hydrolysis Method - Permatasari, Mauludiah; Anggraeni, Shinta Ristiana; Triana, Nurul Widji; Muljani, Srie; Sani, Sani (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2026)
Nanocrystalline cellulose (NCC) is a fiber-based material with one dimension in the nanometer scale (1–100 nm), featuring high specific surface area, excellent mechanical strength, and biodegradability. It has great potential as an environmentally friendly polymer filler. This study aims to synthesize nanocrystalline cellulose from cassava stem waste via acid hydrolysis with 32% hydrochloric acid (HCl) and to examine the effects of varying sample weight and HCl volume on particle size and morphology. The process involved delignification using sodium sulfite, bleaching with hydrogen peroxide, and acid hydrolysis. Sample weights (5–9 grams) and HCl volumes (50–90 mL) were varied. PSA results showed the smallest particle size was 5,564.2 nm (5 g, 70 mL) and the largest was 23,132.1 nm (9 g, 50 mL). PDI indicated a more homogeneous particle distribution at higher HCl volumes. SEM analysis revealed that the typical NCC structure had not yet been optimally formed. Therefore, further optimization of the synthesis process is necessary, highlighting the importance of refining each step to achieve desired nanomaterial properties.